HEART FATTY ACID BINDING PROTEIN SEBAGAI PETANDA BIOLOGIS DIAGNOSIS SINDROM KORONER AKUT - Ira Puspitawati; I Nyoman G Sudana; Setyawati Setyawati; Usi Sukorini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Heart-Fatty Acid-Binding Protein (H-FABP) is a membrane-bound protein that facilitates transport of fatty acids from the blood intothe heart. It is a low molecular weight cytoplasmic protein. Because of its small size and location, it is released rapidly into the bloodfollowing myocardial damage. The H-FABP levels rise as early as between 1−3 hours after the onset of Acute Coronary Syndrome, thepeak situation between 6−-8 hours, and returns to normal within 24 hours. The purpose of this study was to know the cut-off value ofHeart Fatty Acid Binding Protein with a sensitivity of at least 90% in patients with acute coronary syndrome in the Dr. Sardjito HospitalYogyakarta. The researchers undertook a cross sectional evaluation of 75 consecutive patients admitted with acute chest pain suggestiveof acute coronary syndrome (ACS). The H-FABP was measured by using immunoturbidimetry assay methods. The receiver operatingcharacteristic (ROC) analysis was calculated for the cut off point, sensitivity and specificity estimation. A total of 75 patients (59 in theACS group and 16 in the control group) were included in this study, and the majority of the ACS group (64 [76.2%]) were male patientswith AMI, 20 (26.7%) had an ST-elevation myocardial infarction and the rest (21 [28%]) had a non–ST-elevation myocardial infarction.The optimized cut-off obtained for h-FABP was 15 ng/mL, showing a sensitivity and specificity of the H-FABP assay for detecting ACSas 98.31 (95% CI 90 to 100) and 93.75% (95% CI 86 to 99), respectively. The areas under the receiver operator characteristic (ROC)curves to distinguish ACS from non-ACS were 0.983 (95% CI: 0.927– 0.999) for H-FABP. The optimized cut-off obtained for H-FABPwas 15 ng/mL, showing a 98.31% sensitivity and 93.75% specificity for detecting ACS in the Dr. Sardjito Hospital Yogyakarta.